Identifikasi Jamur Mikoriza Arbuskula (JMA) Pada Tanah Gambut Bekas Terbakar Di Kota Pekanbaru Provinsi Riau - Sayuti, Irda; Lubis, Eva Rahmayanti (Jurnal Pilar Sains, 2011)
This research done as a mean to identifies species of Mikoriza Arbuskula and density found incombustible secondhand peat soil in town Pekanbaru, Riau. Determining the location of arandom sampling conducted at the location of burned peat that occurred in August 2009,the sites are located at: Arengka 2 kecamatan payung Sekaki street, Tuanku Tambusaikecamatan payung Sekaki street and Delima ujung kecamatan Tampan street. Every locationof observation is taken by 1 check with 3 times fairish restating 30x30 cm with depth of 15 cm assampling. Out of three combustible secondhand peat soil locations investigated, found 5 species ofMikoriza Arbuskula that is: Glomus proliferum, Glomus intraradices, Glomus sp. 1, Glomus sp. 2and Acaulospora tuberculata. Then species of Mikoriza Arbuskula having as of wide swampy forestcompared to other Mikoriza Arbuskula´s species is group from Genus Glomus. Because in generalGlomus very lenient to condition of extreme area.